Analisis Komparatif Teori Konsumsi Mazhab Monzer Kahf, Abdul Manan dan Yusuf Al-Qardhawi - Naysa Buri; Nurizal Ismail; Sholahuddin Al-Ayubi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to compare consumption theories according to the perspectives of Monzer Kahf, Abdul Manan, and Yusuf Al-Qardhawi. It employs a formal literature review method to compare the consumption theories of these three figures, utilizing qualitative analysis of relevant literature and texts such as books, articles, and journals authored by the three thinkers. The research findings indicate that Monzer Kahf, Abdul Manan, and Yusuf al-Qardhawi have different approaches to understanding consumption in the context of Islamic economics. Monzer Kahf emphasizes the importance of consuming goods without extravagance or wastefulness and paying attention to the benefits of those goods. Abdul Manan underscores the significance of creating fair income and wealth distribution. Meanwhile, Yusuf al-Qardhawi emphasizes the importance of consuming by considering necessary needs, including spending wealth for goodness, avoiding miserliness, combating wasteful actions, and adopting a modest attitude in spending wealth. Thus, the three consumption theories according to the perspectives of Monzer Kahf, Abdul Manan, and Yusuf Al-Qardhawi share similarities in emphasizing the importance of moderate consumption, avoiding miserliness, and meeting the basic needs of individuals and society.